ABOUT THE BHOPAL SCHOOL OF SOCIAL SCIENCES (BSSS) - The Bhopal School of Social Sciences (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The Bhopal School of Social Sciences was founded in the year 1972-at the initiative of Most Rev Dr. Eugene D’ Souza, the then Archbishop of Bhopal-in response to the need of the time for a broadbased, job-oriented curriculum with an initial focus on social service and entrepreneurship. The institution is supported and managed by the Archdiocese of Bhopal through the BSSS Foundation Society chaired by the Archbishop of Bhopal. Since its inception, the College has adopted an integrated and comprehensive approach to learningin order to achieve academic excellence. This vision has been the cornerstone of our growth in the last 49 years as we gradually adopted new programs, initiated innovative learner strategies, and took bold steps to go beyond the prescribed curriculum with a view to transform knowledge into affirmative action. Initially known for its Social Sciences and Management courses, the College grew and diversified with the introduction of courses in Commerce, Information & Technology, Science and Physical Education. Catering to the high demand for Commerce subjects, the College offers a wide range of options including an honours course as well as specializations in Foreign Trade, Travel and Tourism, Banking and Insurance, Taxation, Computer Applications, Advertising, Sales Promotion & Sales Management. Subsequently, post graduate courses in Social work, English Literature, Commerce, Economics, Computer Applications, Sociology, Political Science, Psychology and Business Administration followed. Presently, our Humanities portfolio includes 4 undergraduate honours programs in Social Work, Economics, English literature and Psychology. The College also runs two international MBAs through collaboration with Assumption University, Bangkok and Under Graduate Courses in collaboration with Concordia College, USA. We also have tie-up with IMA, US and ACCA, UK. With the objective of widening the educational experience of our students as well as to encourage inter-disciplinary learning, the College offers 41 certificate courses and 6 diploma courses. The Business English Certificate course of Cambridge University offered at three levels: Preliminary, Vantage and Higher further enhance the value of the degree courses. The strength of our ideology was put to a litmus test, first in 2006, and subsequently in 2012 and 2017 by NAAC. On all the three occasions, our claim to excellence was validated through an ’A’ Grade certificate. The College has already been granted autonomy in May 2013 and extension of autonomy in 2019 for another term of five years. Our endeavours have always been encouraged and guided by our Chairman, Most Rev. Dr Leo Cornelio, the Archbishop of Bhopal Diocese. Spearheaded by his vision of global education, peaceful resolution of conflict, social equality and high standards of personal conduct, we hope to scale new heights in the world of academia and create a conducive environment for intellectual, social, moral and spiritual growth of the world we live in.